IMPLEMENTASI LATIHAN MENGGENGGAM BOLA KARET PADA LANSIA PASCA STROKE DENGAN KETERBATASAN AKTIVITAS FISIK - Destria Efliani; Ary Oktora Sri Rahayu; Eva Mayasari; Nurdiana Hasanah; Ria Permata Sari; Zahira Inayah Rinzadi; Rahmadhila Hendri (Jurnal Pengabdian Masyarakat 360 Derajat, 2026)
Stroke is a leading cause of long-term disability in the elderly, resulting in decreased motor function, muscle weakness, and limited physical activity. This condition reduces the independence of the elderly in carrying out daily activities, necessitating simple and sustainable rehabilitation efforts. This community service activity aims to improve the knowledge, skills, and functional abilities of post-stroke elderly people through the implementation of rubber ball grip exercises at the UPT Social Services for the Elderly in Khusnul Khotimah Pekanbaru. The methods used include health education, demonstrations, direct practice, mentoring, and monitoring and evaluation. The activity involved 20 post-stroke elderly people with limited physical activity. The results showed an increase in the level of knowledge of participants from the good category by 20% to 90% after the education. As many as 85% of participants were able to perform the exercises independently with the correct technique, while 95% of participants were willing to do the exercises regularly. In addition, there was an increase in the ability to grip a rubber ball firmly from 25% to 75% and an increase in the ability to maintain a grip for 5–10 seconds from 30% to 80%. This activity shows that rubber ball gripping exercises are a simple rehabilitation intervention that is effective in improving motor function and physical activity in post-stroke elderly people.